2018
DOI: 10.2217/rme-2017-0152
|View full text |Cite
|
Sign up to set email alerts
|

Human Adipose-Derived Mesenchymal Stem Cells for Osteoarthritis: A Pilot Study with Long-Term Follow-Up and Repeated Injections

Abstract: The preclinical study established the safety and efficacy of haMSCs. Intra-articular injections of haMSCs were safe and improved pain, function and cartilage volume of the knee joint, rendering them a promising novel treatment for knee osteoarthritis. The dosage of 5 × 10 haMSCs exhibited the highest improvement (ClinicalTrials.gov Identifier: NCT01809769).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
165
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(175 citation statements)
references
References 48 publications
8
165
0
2
Order By: Relevance
“…Interestingly, in pioneering studies on OA patients, SVF injection was able to stimulate partial regeneration of the articular cartilage, as described by positive changes in the imaging outcomes (MRI or CT) [61][62][63][64][65]. Consistently, in the last years, few clinical trials based on intra-articular injection of autologous ASCs in OA joints reported improvement in pain, function and cartilage volume [66,67]. These effects on cartilage may be, at least partially, ascribed to those protective molecules and miRNAs we found in the ASC secretome.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, in pioneering studies on OA patients, SVF injection was able to stimulate partial regeneration of the articular cartilage, as described by positive changes in the imaging outcomes (MRI or CT) [61][62][63][64][65]. Consistently, in the last years, few clinical trials based on intra-articular injection of autologous ASCs in OA joints reported improvement in pain, function and cartilage volume [66,67]. These effects on cartilage may be, at least partially, ascribed to those protective molecules and miRNAs we found in the ASC secretome.…”
Section: Discussionmentioning
confidence: 91%
“…As already reported for BMSCs, repeated injections of 50 × 10 6 ASCs allowed for significant improvements in terms of pain and knee function. An additional injection provided at 48 weeks after the previous ones was able to generate another improvement, positively affecting also the cartilage volume [ 38 ].…”
Section: Clinical Outcomes Of Mscs In the Treatment Of Oamentioning
confidence: 99%
“…Trials conducted to assess the benefit of ADSC-derived treatment of wounds, have only reached pilot study or phase I stage in simple cutaneous wounds Holm et al, 2018); however, in Crohn's disease-related peri-anal fistulae, a phase III study (Panes et al, 2018) has shown good efficacy. Similarly, good efficacy has been shown in phase I and IIa studies involving treatment of osteoarthritis (Song et al, 2018) and phase III studies are ongoing at the time of writing (Table 3). Finally, promise has also been shown in central nervous system disease [phase I and II studies in multiple sclerosis (Fernandez et al, 2018)].…”
Section: Summary Of Adsc-derived Clinical Trialsmentioning
confidence: 85%